THE IMPORTANCE OF AXIOLOGICAL APPROACH IN FORMING LEADERSHIP COMPETENCE IN STUDENTS (Academicia Globe: Inderscience Research, 2022)
This article presents ideas about the importance and role of the axiological approach in the formation of leadership competence in students.